Անձի Ես-կոնցեպցիայի ձևավորումը - Առաքելյան, Սիրինա (Զանգակ հրատ.)
In the article the author generally analyses different authors’ opinions concerning the Selfconcept formation. In psychological literature many aspects and factors are mentioned and pointed out (prenatal period events, welcome or unwelcome child, mother’s and significant others’ attitude, biological features etc.). In the article a detailed analysis of the most important factors, which can influence the formation and the development of different components of Self-concept is presented. В статье автор анализирует разные подходы авторов, относительно формирования Я-концепции. В психологической литературе разными авторами подчеркивается значимость многих аспектов и факторов в формировании Я-концепции (события пренатального периода, желанный или нежеланный ребенок, отношение матери и значимых других, биологические особенности и т.д.). В статье дается подробный анализ наиболее важных факторов, которые могут оказать влияние на формирование и развитие различных компонентов Я-концепции.
Keywords: Հոգեբանություն